ANALISIS PSIKOLINGUISTIK FORENSIK PADA KASUS AGUS “BUNTUNG” - Niswariyana, Ahyati Kurniamala; Susanti, Pipit Aprilia (Prosiding Seminar Nasional Bahasa Ibu; Vol 2 No 1 (2025): Prosiding Seminar Nasional Bahasa Ibu 2024/2025, 2025)
This study aims to analyze the speech used in sexual harassment cases in order to identify language patterns, manipulative strategies, and indications of pressure or threats in the interaction between the perpetrator and the victim in the Agus “Buntung” case. I Wayan Agus Suartama, known as Agus “Buntung”, is a disabled man from Mataram, West Nusa Tenggara. The Agus Buntung case surfaced in mid-October 2024. Agus Buntung has now been declared a suspect in a sexual harassment case involving 17 victims. In carrying out his actions, Agus used emotional manipulation tricks on his victims. Emotional manipulation is a form of psychological manipulation in which people try to control other people's emotions through verbal language. This is often done through persuasion, coercion, or even emotional blackmail. The data used in this study is the verbal language data expressed by Agus Buntung. Qualitative methods were used in analyzing the data. The data found were analyzed using psychological theory and forensic linguistic theory. The psychological theory used to analyze this data is the grooming behavior theory with techniques to manipulate its victims. Forensic linguistic theory is used to describe whether Agus' verbal language implies the perpetrator's intention in carrying out his actions. The results found are that it is true that Agus used emotional manipulation tricks on his victims as evidenced by the manipulative language used. That from the existing language data, Agus uses implied language indicating sexual harassment.